Improving Students’ Motivation And Students’ Achievement In Explaning Text By Using Down Payment Scoring (Dps) At Eight Grade Students’ In Smp Negeri 2 Bayang Kecamatan Bayang - Maizarni Maizarni (Fakultas Sastra Universitas Ekasakti, 2018)
Increased Motivation and Learning Outcomes Explanation Text in Class VIIIA of SMP Negeri 2 Bayang in Class VIIISemester 2. Problems on the study of this class action is: Are Down Payment Scoring (DPS) as a management technique value can increase motivation and student learning outcomes Class VIII SMP Negeri 2 Bayang the 2nd half in the text explanation?, The purpose of this research is to improve motivation and student learning outcomes Class VIIIA of SMP Negeri 2 Bayang, semester 2 in the text explanation. The benefits of this research include (1) the student is improving motivation and learning outcomes of students explanation text, (2) for teachers, can find a way of managing a proper assessment to improve motivation and learning outcomes text explanation. This study was conducted in two cycles, namely, in cycle 1, the action taken is the implementation of DPSin responding to the meaning of a text explanation (read) and the second cycle of the action taken is the implementation of DPS in the monologue of the explanation text (speech). The research was carried out for 3 months, namely from March until May 2017, the subject of classroom action research conducted on VIIIA grade Junior High School 2 Bayang a total of 30 students of SMP Negeri 2 Bayang Semester 2. Methods and study design using the method description. Analysis of the data used is descriptive analysis by comparing the value pre cycles, with the first cycle and the second cycle. The results showed that the students' motivation Pre cycle increased significantly from 13.33% to 56.67% in the first cycle and increased to 76.67% in Cycle II.While the study results to understand text explanation significant increase of 57% (17 students) completed the stage Prasiklus to 80% (24 students) completed the first cycle and increased to 97% (2 9 students) completed the second cycle.The achievement of the target value also increased from 8 students (32%) to 15 students (52%) in Cycle II. Thus, the hypothesis that the authors ask in this class action research